2019
DOI: 10.1111/ijac.13253
|View full text |Cite
|
Sign up to set email alerts
|

Development of ethylene glycol‐Cr2AlC nanofluid for thermal management in the automotive sector

Abstract: The current study is focused on the development of a novel nanofluid for efficient thermal management in the automotive sector. For this, novel Cr 2 AlC-based nanofluids were prepared and its properties were compared with conventional nanofluids prepared under similar condition. h-BN, MoS 2 , Al 2 O 3 , and Cr 2 AlC powders of <60 nm were prepared by high energy ball mill and were added into the EG fluid in 0.25 and 0.50 wt%. The nanofluids were investigated for viscosity, flash point, fire point, thermal cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The heat transfer enhancement in microchannel was studied using Al 2 O 3 nanofluids by Munimathan et al 29 The enhancement in heat transfer compared to water was found to be 23.06% and 32.8% for .1% and .25% volume concentrations. Davis et al 30 reported the thermal conductivity of EG and EG added with .50 wt.% of Al 2 O 3 nanoparticles. The thermal conductivity was measured in the temperature range of 300 to 360 K. They obtained .25 and .36 W/mK respectively for EG and Al 2 O 3 nanofluids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The heat transfer enhancement in microchannel was studied using Al 2 O 3 nanofluids by Munimathan et al 29 The enhancement in heat transfer compared to water was found to be 23.06% and 32.8% for .1% and .25% volume concentrations. Davis et al 30 reported the thermal conductivity of EG and EG added with .50 wt.% of Al 2 O 3 nanoparticles. The thermal conductivity was measured in the temperature range of 300 to 360 K. They obtained .25 and .36 W/mK respectively for EG and Al 2 O 3 nanofluids.…”
Section: Introductionmentioning
confidence: 99%
“…The enhancement in heat transfer compared to water was found to be 23.06% and 32.8% for .1% and .25% volume concentrations. Davis et al 30 . reported the thermal conductivity of EG and EG added with .50 wt.% of Al 2 O 3 nanoparticles.…”
Section: Introductionmentioning
confidence: 99%